Actualisation of Practical Lessons through Assessment in Civil Technology - Mtshali, Thokozani Isaac; Ramaligela, Sylvia Manto; Makgato, Moses (Journal of Technical Education and Training, 2021)
Learning Civil Technology at the school level is not about discovering new or unknown ideas. Rather it is about capacitating learners with hands-on practical skills that are known and needed in engineering as well as artisans’ sectors. The purpose of this study is to explore how Civil Technology teachers actualise practical lessons through assessment. Purposive sampling was used to identify 5 teachers of Ekurhuleni district schools in the Gauteng Province to participate in this study. Observation, Document analysis and interview instruments were used as data-collection methods. Assessment theories were used as a conceptual framework to understand how various assessments are used to execute practical lessons of Civil Technology. The study found that only assessment for learning was used well by teachers, however, assessment as learning, as reflective, of learning and competency based assessment were used for compliance purposes and sometimes misunderstood as a tool to strengthen practical activities. It can be concluded that most Civil Technology teachers do not perceive assessment as a mechanism to strengthen hands-on practical activities. This study recommends that Civil Technology teachers should be assisted on how to appropriately use assessment strategies to cater for all learning needs associated with practical skills.